Do we know the band gap of lithium niobate? - Thierfelder, Christian; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physica Status Solidi C)
Given the vast range of lithium niobate (LiNbO3) applications, the knowledge about its electronic and optical properties is surprisingly limited. The direct band gap of 3.7 eV for the ferroelectric phase – frequently cited in the literature – is concluded from optical experiments. Recent theoretical investigations show that the electronic band‐structure and optical properties are very sensitive to quasiparticle and electron‐hole attraction effects, which were included using the GW approximation for the electron self‐energy and the Bethe‐Salpeter equation respectively, both based on a model screening function. The calculated fundamental gap was found to be at least 1 eV larger than the experimental value. To resolve this discrepancy we performed first‐principles GW calculations for lithium niobate using the full‐potential linearized augmented plane‐wave (FLAPW) method. Thereby we use the parameter‐free random phase approximation for a realistic description of the nonlocal and energydependent screening. This leads to a band gap of about 4.7 (4.2) eV for ferro(para)‐electric lithium niobate.

Ab initiog-tensor calculation for paramagnetic surface states: hydrogen adsorption at Si surfaces - Gerstmann, Uwe; Rohrmüller, M.; Mauri, F.; Schmidt, Wolf Gero (physica status solidi (c))

Optical anisotropy of Si(111)-(4 × 1)/(8 × 2)-In nanowires calculated fromfirst-principles - Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Chandola, S.; Hinrichs, K.; Gensch, M.; Esser, N.; Fleischer, K.; McGilp, J. F. (physica status solidi (c))

GaN growth on LiNbO3 (0001) - a first-principles simulation - Sanna, Simone; Schmidt, Wolf Gero (physica status solidi (c))

Temperature dependent stability of self-assembled molecular rows - Blankenburg, S.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initio investigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, G. (physica status solidi (c))

Non-polar cubic AlGaN/GaN HFETs grown by MBE on Ar+implanted 3C-SiC (001) - Tschumak, Elena; Lindner, Jörg; Bürger, M.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (physica status solidi (c))
The growth of cubic group III-nitrides is a direct way to eliminate polarization effects, which inherently limit the fabrication of normally-off heterojunction field-effect transistors (HFETs) in GaN technology. HFET structures were fabricated of non-polar cubic AlGaN/GaN hetero layers grown by plasma assisted molecular beam epitaxy (MBE) on free standing 3C-SiC (001). The electrical insulation of 3C-SiC was realised by Ar+ implantation before c-AlGaN/GaN MBE. The structural properties of the epilayers were studied by highresolution x-ray diffraction (HRXRD). HFETs with normally off and normally-on characteristics were fabricated of cubic AlGaN/GaN. Capacitance-voltage (CV) characteristics of thegate contact were performed to detect the electron channel at the c-AlGaN/GaN hetero interface.

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))